STRATEGI KEAMANAN EKONOMI CHINA TAHUN 2013 DALAM MEMPERTAHANKAN KEPENTINGAN NASIONAL DI JALUR SAMUDERA HINDIA - Cahyaningrum, Devita Ayu; GPH. Dipokusumo, Setyasih Harini, (Solidaritas, 2017)
STRATEGI KEAMANAN EKONOMI CHINA TAHUN 2013 DALAM MEMPERTAHANKAN KEPENTINGAN NASIONAL DI JALUR SAMUDERA HINDIADevita Ayu CahyaningrumSetyasih Harini, S.IP, M.SiDrs. GPH. Dipokusumo, M.SiProgram Studi Ilmu Hubungan Internasional Fakultas Ilmu Sosial Dan Ilmu PolitikUniversitas Slamet Riyadi SurakartaÂ Â ABSTRACTThis research aimed to discuss Chinese economic strategy in 2013 to defend its national interest in Indian Ocean. China encountered economic decline that could trigger economic deceleration and increase unemployment rate likely harmful to the national stability and the fulfillment of its domestic energy demand for industry, using national security theory involving economic security and national interest theory. The research method employed in this thesis was qualitative one with document-based technique of collecting data through descriptive elaboration and using secondary data collected through literature study.Â Through analyzing the Chinese economic security strategy in 2013 in defending national interest in Indian Ocean channel, the author found that Chinese economic strategy to defend national interest was to employ Indian Ocean channel to connect trade from Chinaâs main land to South East Asian, South Asian, and African countries and to make it the energy supplying channel for Chinese industry through harbor infrastructure cooperation and People Liberation Army Navy (PLAN)âs role to protect the trade channel and oil supply from disruption and threat in Indian Ocean and to improve alutsista (Instrumental weapons system), particularly that of Navy for the smoothness and security of trading and energy supply. The Chinese economic strategy in defending national interest in Indian Ocean in 2013 through constructing harbor in South East Asia, South Asia, and Africa optimized the role of People Liberation Army Navy (PLAN) and improved the Navyâs alutsista.Keywords: economic security, national interest, China